A new species of the genus Anthalona Van Damme, Sinev & Dumont, 2011 (Cladocera: Anomopoda: Chydoridae) from North-East Thailand - Tiang-Nga, Supatra; Sinev, Artem Y.; Sanoamuang, La-Orsri (Zootaxa, 2016)
A new species of Cladocera, Anthalona spinifera sp. nov., is described from North-East Thailand. A. spinifera differs from most species of the genus in the setae of the inner distal lobe on limb I armed by long thin spines and in limb II having very short scraping spines 6–8, a character that is shared only with the South American Anthalona brandorffi (Sinev & Hollwedel, 2002). A. brandorffi differs from A. spinifera sp. nov. in the shape of postabdomen, in much longer posterior setae of valves, in posteroventral angle of valves armed with about 25 setules only, and in shortened setae of endite 2 of limb I. These two species form a separate advanced clade within Anthalona with Amphi-Pacific distribution.